2006
DOI: 10.1080/01926230600611778
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Proliferating Cell Nuclear Antigen Expression and Histomorphometrical Alterations in Cyclosporin A-Induced Gingival Overgrowth in Rats

Abstract: The aim of this study was to investigate the relationship between Proliferating Cell Nuclear Antigen (PCNA) expression and histomorphometrical alterations in cyclosporin A (CsA)-induced gingival overgrowth with or without microbial dental plaque accumulation. Forty male Wistar rats were equally divided into 4 groups; Group I (control); Group II (CsA); Group III (ligature); Group IV (ligature and CsA). After 8 weeks of experimental period, rats were subsequently decapitated and mandibular molars were dissected.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Recent studies about proliferation and apoptosis markers in different forms of drug‐induced gingival overgrowth have conflicting results. The expression of proliferation cell nuclear antigen, one of the most popular proliferation markers, was found to be increased in drug‐induced gingival overgrowth 29,52 . More recently, an increase in mitotic activity as measured by the expression of Ki67 and cyclin‐B1 proliferation markers was found in drug‐induced gingival overgrowth 14,53 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies about proliferation and apoptosis markers in different forms of drug‐induced gingival overgrowth have conflicting results. The expression of proliferation cell nuclear antigen, one of the most popular proliferation markers, was found to be increased in drug‐induced gingival overgrowth 29,52 . More recently, an increase in mitotic activity as measured by the expression of Ki67 and cyclin‐B1 proliferation markers was found in drug‐induced gingival overgrowth 14,53 .…”
Section: Discussionmentioning
confidence: 99%
“…The expression of proliferation cell nuclear antigen, one of the most popular proliferation markers, was found to be increased in drug-induced gingival overgrowth. 29,52 More recently, an increase in mitotic activity as measured by the expression of Ki67 and cyclin-B1 proliferation markers was found in drug-induced gingival overgrowth. 14,53 On the other hand, Shimizu et al 43 reported that epithelial hyperplasia in nifedipine-induced gingival overgrowth is induced not by an increase in proliferation but by the prolongation of cell life through inhibition of apoptosis.…”
Section: Volumetric Densities Of Fibroblasts Collagen Fibers and Blmentioning
confidence: 99%
“…This model is characterized by accumulation of dental plaque and increased infiltration of inflammatory cells that lead to a degradation of periodontal connective tissue and alveolar bone (Keles et al, 2005). In recent years, the effects of CsA therapy on soft tissues of the periodontium have been extensively investigated in vitro (Bartold 1989;Schincaglia et al, 1992) and in vivo (Seymour et al, 1987;Somacarrera et al, 1994;Cetinkaya et al, 2006aCetinkaya et al, , 2006b. It has been reported that 10 mg/kg daily doses of the drug 720 CETINKAYA ET AL TOXICOLOGIC PATHOLOGY provide plasma peak and trough levels of 1000 and 750 ng/ml (Wassef et al, 1985) and blood levels of CsA between 100-400 ng/ml are sufficient to promote immunosupression in animals (rats, dogs, and monkeys) as well as in humans (Fischer and Klinge, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Ca-channel antagonists and Cyclosporine A are known to induce gingival overgrowth in laboratory animals 3 , 4 . Lenz et al 5 reported a dose-related increase in oral squamous carcinoma in a 2-year rat carcinogenicity study with a novel calcium channel antagonist that was not a direct tumorigenic effect of the drug but was attributed to severe periodontal disease due to diet and the class-related gingival overgrowth.…”
mentioning
confidence: 99%